Vitality of The Cities - Sena Işiklar (International Journal of Architectural Engineering Technology, 2017)
The physical formation of city, where all members of society live, is created by non-living and tangible elements such as buildings, roads, public squares, and vegetation. On the other hand, city acquires meaning by the existence of citizens, who reinvigorate it, their behaviours within the city and the interactions between them as well as with the city. The more the citizens are actively present in the streets, the more the city is a vivid and living place. There are many studies on vitality and liveability in urban spaces. In this study, urban vitality is defined according to the information gathered from previous researches. By scrutinizing the definitions of vitality made by Lynch and Jacobs, who are leading figures in the subject of research, social interaction, sense of belongingness, and security, inclusion of different functions, transformability, aesthetics and accessibility were identified as criteria determining the urban vitality. As a result of the study, it is asserted that the cities which bear these qualifications are liveable and vivid places which can maintain their existence.